2011
DOI: 10.1152/ajpregu.00853.2009
|View full text |Cite
|
Sign up to set email alerts
|

Key roles of endothelin-1 and p38 MAPK in the regulation of atrial stretch response

Abstract: Mechanisms regulating stretch response in the left ventricle are investigated in detail but not well understood in atrial myocardium. Hypertrophic growth of atrial myocardium contributes to the pathogenesis of atrial fibrillation. In this study, we sought to elucidate mechanisms of stretch-induced activation of key signaling pathways and hypertrophy-associated genes in rat atria. Stretching of isolated atria induced a rapid increase in phosphorylation of p38 MAPK and ERK and induced a p38 MAPK-dependent increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
3
20
0
2
Order By: Relevance
“…Furthermore, several components of the intracellular signaling cascade responsible for conveying the atrial myocardial stretch response for atrial natriuretic peptide secretion, are shared with those regulating the circadian clock, e.g. protein kinase C and mitogen-activated protein kinase (MAPK) [22], [32], [46][48].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several components of the intracellular signaling cascade responsible for conveying the atrial myocardial stretch response for atrial natriuretic peptide secretion, are shared with those regulating the circadian clock, e.g. protein kinase C and mitogen-activated protein kinase (MAPK) [22], [32], [46][48].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a cross talk between MAPK signaling pathway and hypertrophic genes has been reported. In that, inhibition of the p38 MAPK in cardiac hypertrophied rat resulted in a significant decrease in the expression of b-MHC and several natriuretic peptides, but not in healthy rats [20]. In addition, it has been reported that activation of ERK MAPK induced the expression of hypertrophic genes through stimulation of cardiac transcriptional factor GATA4 [21][22][23][24].…”
Section: Introductionmentioning
confidence: 94%
“…Mechanical stretch of the atrial wall is one of the most potent stimuli for ANP expression and release (Edwards et al, 1988). The signaling molecules in this process include integrins, p38 MAPK and focal adhesion kinase (Kerkela et al, 2011; Peng et al, 2008). To date, many growth factors and vasoactive molecules have been reported to enhance ANP expression and secretion (Ogawa and de Bold, 2014; Potter et al, 2006).…”
Section: Anp As a Biomarkermentioning
confidence: 99%